Search for W' -> tb resonances with left- and right-handed couplings to fermions D0 Collaboration - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Aoki, M.; et al. (Elsevier B.V., 2011)
We present a search for the production of a heavy gauge boson, W', that decays to third-generation quarks, by do Collaboration in p (p) over bar) collisions at root s = 1.96 TeV. We set 95% confidence level upper limits on the production cross section times branching fraction. For the first time, we set limits for arbitrary combinations of left-and right-handed couplings of the W' boson to fermions. For couplings with the same strength as for the standard model W boson, we set the following limits, assuming that there are right-handed neutrinos nu(R) for all three generations with M(W') > m(nu(R)): M(W') > 863 GeV for purely left-handed couplings, M(W') > 885 GeV for purely right-handed couplings, and M(W') > 916 GeV if both left-and right-handed couplings are present. The limit for right-handed couplings improves for M(W') < m(nu(R)) to M(W') > 890 GeV. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Wprime; Resonances; Top quark; Bottom quark; Left-right couplings